Liver Resection in a Tertiary University Hospital in Damascus- trends Related to the Political Strife and Social Crisis - Ahmad, Basel; Marwa, Mohamad Essam; Turkmani, Khaled; Ahmad, Tareq; Baghdadi, Ramez; Aboudamaah, Shaimaa; Alkhatib, Khetam; Ahmad, Mohamad (Asian Pacific Journal of Cancer Care, 2020)
Background: Liver resection is a major operation requires technical training and experience and is expensive for the health care system. Aim: Our aim was to review trends in liver resection in Syria to help our country and others like Syria to understand the hardships for the country’s health care policy. Methods: We analyzed retrospectively the results of 95 patients who underwent a liver resection from January 2009 through December 2015 at our tertiary university hospital in Damascus. Results: The number of annual liver resections increased over this 6 year period, but there were several years during which the numbers were dramatically less, related to the social crisis. Of them, 63 underwent resection for malignant neoplasms (66%) and 30 for non-malignant disorders (32%). Conclusion: Dedication of our surgeons to hepatic surgery is increasing in Syria with mortality rates close to international standards despite the ongoing social unrest and political strife.